Rewriting the Islamic History of the Indian Ocean: A Post-Oriental Critique of Orientalist Historiography - Zubair Zafar Khan; Syed Abdul Fazili; Shahla Manzoor Baba; Sameer Shafi Siddiqi (Arba: Jurnal Studi Keislaman, 2026)
Orientalist historiography has long shaped understandings of Islamic history in the Indian Ocean region through a diffusionist paradigm that positions the Middle East as the epicenter of the spread of Islam and coastal communities in South Asia, Southeast Asia, and East Africa as passive recipients of external influences. Despite the development of global history and connected histories, several classical orientalist narratives still influence interpretations of the Islamization process in the region. This article aims to analyze the epistemological biases in orientalist historiography on Indian Ocean Islam and to reconstruct alternative understandings of the Islamization process, scholarly networks, and socio-religious mobility through a post-orientalist perspective. This research employs qualitative methods grounded in critical historiography, analyzing classical orientalist works and contemporary studies on maritime Islamic history through discourse analysis and epistemological critique. The results show that orientalist historiography tends to reproduce Eurocentric assumptions and a center-periphery model that simplifies the complexity of Islamic history in the Indian Ocean region. Islamization took place through transregional networks connecting major ports, the mobility of scholars, traders, and diaspora communities who played active roles in the exchange of ideas, religious practices, and intellectual authority. Interregional interactions have led to processes of adaptation, negotiation, and cultural hybridization that shape local Islamic traditions, all of which are by global networks. The Indian Ocean represents a multipolar and dialogical space of Islamic connectivity, while also offering a historiographical reconstruction that positions regional actors as central elements in the formation of maritime Islamic history.